2016
DOI: 10.1016/j.watres.2015.12.054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microalgal N and P composition on wastewater nutrient remediation

Abstract: Microalgae have demonstrated the ability to remediate wastewater nutrients efficiently, with methods to further enhance performance through species selection and biomass concentration. This work evaluates a freshwater species remediation characteristics through analysis of internal biomass N:P (nitrogen:phosphorus) and presents a relationship between composition and nutrient uptake ability to assist in species selection. Findings are then translated to an optimal biomass concentration, achieved through immobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 28 publications
4
76
1
Order By: Relevance
“…The duration of each experiment varied according to the days that the culture was maintained in pseudosteady state ( Table 2) In order to inhibit nitrification, allylthiourea (ATU) was added to the culture to maintain a concentration of 1-5 mgꞏL -1 in the PBRs (González-Camejo et al, 2018a). In addition, the pH set-point value of the culture (7.5) made ammonia volatilisation and phosphorus precipitation be negligible (Whitton et al, 2016) so that microalgae were considered as the main responsible for nutrient recovery.…”
Section: Experimental Periodsmentioning
confidence: 99%
“…The duration of each experiment varied according to the days that the culture was maintained in pseudosteady state ( Table 2) In order to inhibit nitrification, allylthiourea (ATU) was added to the culture to maintain a concentration of 1-5 mgꞏL -1 in the PBRs (González-Camejo et al, 2018a). In addition, the pH set-point value of the culture (7.5) made ammonia volatilisation and phosphorus precipitation be negligible (Whitton et al, 2016) so that microalgae were considered as the main responsible for nutrient recovery.…”
Section: Experimental Periodsmentioning
confidence: 99%
“…In addition, the biomass production, growth, and fucoxanthin productivity of P. tricornutum depend on nutrient concentration and the balance between relevant nitrogen and phosphorus (N/P) species in the media (Choi and Lee 2015;Whitton et al 2016;McClure et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant inverse correlation (p < 0.01) exists between the biomass produced and total nitrogen concentration in the water. Several authors have reported the need for a balanced N:P ratio when using wastewater as the growth medium for microalgae for increased growth and nutrient removal [26,30]. In this study, the total nitrogen concentration far exceeded the total phosphorus concentration at the NWWTW with its optimal N:P of 44.2 exceeding the optimal range of 6.8 to 10 [28].…”
Section: Discussionmentioning
confidence: 65%